Field and laboratory trials of 400GBASE‐LR8 over fibre distances up to 35 km. Issue 22 (1st November 2018) - Zhou, Y.R.; Smith, K.; Gilson, M.; Brooks, P.; Cole, C.; Yu, C.
Abstract : Successful experimental demonstration and field trial of 400GBASE‐LR8 is reported based on 4‐level pulse amplitude modulation format over standard G.652 single‐mode fibre using CFP8 pluggable optical transceivers. Stable long‐term error‐free performance of 400GBASE‐LR8 optical signal over fibre spools of varying lengths up to 35 km is demonstrated, which is significantly longer than the IEEE standard 802.3bs specification of 10 km reach. For the first time, error‐free full throughput performance of 400GBASE‐LR8 over a 27 km field fibre link including optical patch panels through operational exchanges is also demonstrated. The results demonstrate that this early 400GBASE‐LR8 client technology is suitable for practical network deployment scenarios and has potential for even longer reach beyond the 10 km specification.